Pengaruh Capacity Building dan Motivasi Kerja terhadap Produktivitas Kerja Pegawai Puskesmas Limo - Lutfia Ferdiana Putri; Ratnawaty Marginingsih (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
UPTD Puskesmas Limo is a regional public health center for Limo sub-district which is underpinned by the health department and health facilities managed by the local government. The health Dcenter has the responsibility of providing primary health services to the people of Limo city. With these demands and types of work, training or employee self-development is needed to hone employees' abilities and work motivation. To find out how much influence capacity building and work motivation have on the productivity of UPTD Puskesmas Limo employees, this title was raised. This study uses quantitative methods using non-probability sampling techniques, namely saturated sampling techniques. The sample of this study amounted to 50 people. Then tested quantitative statistical analysis, multiple linear regression analysis and coefficient of determination analysis using a data processing program, namely SPSS 25 software. This study found the results using the t test stated that Capacity Building partially has a significant effect on work productivity with a significant level of 0.02 <0.05 and the t test results of 3.021> 2.008. and work motivation partially has a positive and significant effect on work productivity with a significant value of 0.01 <0.05 and a t test value of 3.146> 2.008 Capacity Building d is a positive and significant effect on work productivity.